A CFD parametric study on the performance of a low-temperature-differential γ-type Stirling engine. (December 2015) - Chen, Wen-Lih; Yang, Yu-Ching; Salazar, Jose Leon
Highlights: A parametric study on a low-temperature-differential Stirling engine has been conducted by using CFD. The effects of three geometric and two operational parameters on engine performance have been investigated. It is found that each parameter produces different effects except power piston stroke and power piston radius. The results are useful for guiding the design of new low-temperature-differential Stirling engines. Abstract: An in-house CFD code has been applied to a low-temperature-differential (LTD) γ -type Stirling engine to understand the effects posed by several geometrical and operational parameters on engine performance. The results include variations of pressure, temperature, and heat transfer rates within an engine cycle as well as variations of engine's power and efficiency versus these parameters. It is found that power piston stroke and radius influence engine performance very similarly, and power and efficiency both increase as these two parameters increase. In fact, the effects of the two parameters can be assimilated into those by the parameter of compression ratio. The stroke of displacer is observed to affect strongly on heat input but weakly on power, thus causing the efficiency to decrease as it increases. As expected, both power and efficiency increase as temperature difference between the hot and cold ends increases. Lastly, engine speed is observed to pose strong positive effects on power but exert weak effects on efficiency. This study reveals the effects produced by several important parameters on engine performance, and such information is very useful for the design of new LTD Stirling engines.